Interjurisdictional employment in Canada, 2002 to 2019 - Hanqing Qiu (Economic and Social Reports)
This article presents an overview of inter-jurisdictional employment in Canada over the 2002-to-2019 period. Inter-jurisdictional employees are individuals who maintain their primary residence in their home province or territory while working outside this province or territory. The results are based on Statistics Canada’s Canadian Employer-Employee Dynamic Database and pertain to employees aged 18 or older earnings at least $1,000 in 2016 dollars within Canada.